Membangun Kesadaran tentang Osteoporosis dan Risiko Jatuh pada Kelompok Wreda: - - Widowati, I Gusti Ayu Rai; Manuaba, I.A Ratih Wulansari; Suryaningsih, N.P Aryati; Sutema, I.A Manik Partha; Maharjana, I.B.N; Dewi, D.A.P Satrya (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Prioritising our health and well-being becomes more crucial as we become older. Bone health is a significant factor that is sometimes overlooked, particularly in light of the risk of osteoporosis and the possibility of falls in the senior population. Purpose: The goal of this community service project is to educate senior citizens about osteoporosis and how it increases their risk of falling. Method: On Saturday, November 9, 2023, at the office of the Republic of Indonesia Wredatama Association, Denpasar City, the activity was carried out using field education approaches. This program is part of National Health Day 2023. Results: 100 seniors took part in overall. The results of the survey demonstrated that participants' knowledge split into two categories: good (24.0%) and adequate (76.0%). In conclusion, by providing seniors with information about the causes, preventative actions, and available resources, we may help them live safer and healthier lives.